Transformational Leadership Strategies of the School Principal in Implementing the Independent Curriculum at SMP Negeri 7 Dedai, Sintang Regency - Agusnani Agusnani; Usman Radiana; Wiwik Yunitaningrum; Sri Maryuni; Marinu Waruru (JPMI (Jurnal Pendidikan Matematika Indonesia), 2026)
This study aims to explore the transformational leadership strategies of the school principal in implementing the Independent Curriculum at SMP Negeri 7 Dedai, Sintang Regency. The research employed a qualitative descriptive approach with participants including 1 principal, 4 vice-principals, and 1 administrative staff, selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using Miles and Huberman’s model through data reduction, presentation, and verification, with triangulation of sources and techniques. The results indicate that the principal applied transformational leadership strategies by emphasizing the development of a vision and mission aligned with the Independent Curriculum, motivating teachers through support, training, and constructive supervision, and empowering all stakeholders, including administrative staff and parents. The strategies also included a personal approach to teachers to develop their competencies, creativity, and innovation, while fostering a collaborative, adaptive, and innovative school culture. The implementation of these strategies positively impacted the school environment and work culture, evident in increased teacher participation, project-based learning methods, professional competency development, and the integration of the Pancasila Student Profile values in curricular, co-curricular, and extracurricular activities. The success of implementing the Independent Curriculum is reflected in both quantitative indicators, such as improved student average scores and competition participation, and qualitative indicators, including student independence, self-confidence, and critical thinking skills. The study concludes that the principal, as a pedagogical leader, inspires, facilitates innovation, and creates a learning environment that supports the goals of the Independent Curriculum. These findings are expected to provide theoretical contributions to educational leadership studies and practical recommendations for principals to enhance teaching quality and teacher empowerment in secondary schools.Strategi Kepemimpinan Transformasional Kepala Sekolah Mewujudkan Kurikulum Merdeka di SMP Negeri 7 Dedai Kabupaten SintangABSTRAKPenelitian ini bertujuan untuk mengeksplorasi strategi kepemimpinan transformasional kepala sekolah dalam mewujudkan Kurikulum Merdeka di SMP Negeri 7 Dedai, Kabupaten Sintang. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek penelitian meliputi 1 kepala sekolah, 4 guru wakil kepala sekolah, dan 1 staf administrasi, yang dipilih melalui purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman melalui reduksi, penyajian, dan verifikasi data dengan triangulasi sumber serta teknik. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan strategi kepemimpinan transformasional dengan menekankan pembentukan visi dan misi yang selaras dengan Kurikulum Merdeka, motivasi guru melalui dukungan, pelatihan, dan supervisi konstruktif, serta pemberdayaan seluruh pemangku kepentingan, termasuk staf administrasi dan orang tua. Strategi ini juga mencakup pendekatan personal terhadap guru untuk mengembangkan kompetensi, inovasi, dan kreativitas, sekaligus menciptakan budaya sekolah yang kolaboratif, adaptif, dan inovatif. Implementasi strategi tersebut berdampak positif pada lingkungan sekolah dan budaya kerja, terlihat dari peningkatan partisipasi aktif guru, pengembangan metode pembelajaran berbasis proyek, peningkatan kompetensi profesional, serta penerapan nilai Profil Pelajar Pancasila dalam kegiatan intrakurikuler, kokurikuler, dan ekstrakurikuler. Keberhasilan implementasi Kurikulum Merdeka di sekolah ini juga tercermin pada pencapaian indikator kuantitatif, seperti peningkatan rata-rata nilai siswa dan partisipasi dalam kompetisi, serta indikator kualitatif, seperti kemandirian, kepercayaan diri, dan kemampuan berpikir kritis peserta didik. Penelitian ini menyimpulkan bahwa kepemimpinan transformasional kepala sekolah berperan sebagai pemimpin pedagogis yang menginspirasi, memfasilitasi inovasi, serta membangun lingkungan belajar yang mendukung tujuan Kurikulum Merdeka. Temuan ini diharapkan memberikan kontribusi teoritis bagi pengembangan ilmu kepemimpinan pendidikan dan manfaat praktis sebagai rekomendasi bagi kepala sekolah dalam meningkatkan kualitas pembelajaran dan pemberdayaan guru di sekolah menengah.Kata Kunci :kepemimpinan transformasional; kepala sekolah; Kurikulum Merdeka; motivasi guru; pengembangan kompetensi; budaya sekolah